Laparoscopic transabdominal preperitoneal repair of concurrent spigelian and groin hernias: a rare case - Oak, Aditya C.; Kalikar, Vishakha R.; Patel, Ankur K.; Patankar, Roy V. (International Surgery Journal, 2021)
Spigelian hernia is a rare type of abdominal wall hernia due to congenital defect in the transversus aponeurosis fascia. It has a prevalence of 2%. Traditionally, an anterior hernioplasty was used to repair these defects. Only a few cases have been reported in the literature. Here we discuss a case of a 66 year old female with chronic lower abdominal pain with swelling in left inguinal area diagnosed with spigelian hernia on ct scan along with left direct hernia as well as left femoral hernia found incidentally and repaired using totally extra peritoneal single mesh repair.